STATUS DOSEN PADA PERGURUAN TINGGI SWASTA YANG BERUBAH STATUS MENJADI PERGURUAN TINGGI NEGERI (Lex Jurnalica, 2021)
ABSTRACT Changing the status of private universities to new state universities raises problems, among others, regarding legal protection for lecturers and education personnel. This research raises the following problems: 1). What is the legal effect on the status of PTS lecturers who change their status to become New State Universities? ; 2). How is the legal protection for Lecturers at Private Universities who change their status to State Universities. This study uses a normative legal research method. The author conducts research based on data obtained through literature study such as books and statutory regulations. In this study the authors conducted an analysis related to the status of Lecturers of Private Higher Education (PTS) who were appointed as Government Employees with a Work Agreement (PPPK) based on Presidential Decree Number 10 of 2016 concerning Lecturers and Educational Personnel at New State Universities. As a result of the change in the status of private universities, the next question is what about the problem of legal protection for Lecturers and Education Personnel who change their status to Government Employees with a Work Agreement. The rights of lecturers and educational staff who are the author of the research, among others; salary, leave, protection (social security), and their competency development. Keywords: Changes in College Status, Lecturer Status, Government Employees with Work Agreement (PPPK), Legal Protection ABSTRAK Perubahan status Perguruan Tinggi Swasta menjadi Perguruan Tinggi Negeri Baru menimbulkan masalah antara lain tentang perlindungan hukum terhadap Dosen dan Tenaga Kependidikan. Penelitian ini, mengemukakan permasalahan yaitu: 1). Bagaimana akibat hukum terhadap status Dosen PTS yang berubah statusnya menjadi Perguruan Tinggi Negeri Baru ? ; 2). Bagaimana perlindungan hukum terhadap Dosen pada Perguruan Tinggi Swasta yang berubah status menjadi Perguruan Tinggi Negeri. Penelitian ini menggunakan metode penelitan hukum normatif, Penuilis melakukan penelitian berdasarkan data yang diperoleh melalui studi kepustakaan seperti buku-buku serta peraturan perundang-undangan. Dalam penelitian ini Penulis melakukan analisis terkait status Dosen Perguruan Tinggi Swasta (PTS) yang diangkat menjadi Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) berdasarkan Praturan Presiden Nomor 10 Tahun 2016 tentang Dosen dan Tenaga Kependidikan Pada Perguruan Tinggi Negeri Baru. Akibat dari perubahan status Perguruan Tinggi Swasta tersebut maka pertanyaan selanjutnya adalah bagaimana dengan masalah perlindungan hukum terhadap Dosen dan Tenaga Kependidikan yang beralih status menjadi Pegawai Pemerintah dengan Perjanjian Kerja. Hak-hak Dosen dan Tenaga Kependidikan yang Penulis teiliti antara lain; gaji, cuti, perlindungan (jaminan Sosial), dan pengembangan kompetensi mereka. Kata Kunci: Perubahan Status Perguruan Tinggi, Status Dosen, Pegawai Pemerintah dengan Perjanjian Kerja (PPPK), Perlindungan Hukum